Analisa Etika Bisnis Islam Pada Sistem Penjualan Anchoring Effect Di Live E-Commerce - Arofa, Untay; Rohman, Abdur (Program Studi Hukum Ekonomi Syariah (Muamalah), 2025)
This study analyzes the Anchoring Effect in sales systems within live e-commerce from the perspective of Islamic business ethics. This technique is used to influence consumer decisions by presenting a high initial price as an anchor before offering a significant discount, thereby creating a psychological perception of a lower price. In Islamic business ethics, marketing must be based on honesty, transparency, and fairness, so misleading price manipulation can be categorized as tadlīs (fraud) and gharar (uncertainty). This study employs a qualitative method with a Systematic Literature Review (SLR) approach to evaluate how this strategy is applied in live e-commerce. The research findings indicate that transparency, regulations, and consumer education are crucial to ensuring ethical marketing practices that align with Islamic principles. Therefore, policies and regulations are necessary to guide the implementation of the Anchoring Effect, ensuring that it enhances consumer trust without violating the fundamental principles of Islamic business ethics.